The Amino Acid Sensor Eif2ak4/GCN2 Is Required for Proliferation of Osteoblast Progenitors in Mice. (6th July 2020) - Hu, Guoli; Yu, Yilin; Tang, Yuning J; Wu, Colleen; Long, Fanxin; Karner, Courtney M
ABSTRACT: Skeletal stem/progenitor cells (SSPC) are critical regulators of bone homeostasis by providing a continuous supply of osteoblasts throughout life. In response to inductive signals, SSPC proliferate before osteoblast differentiation. Proliferation requires the duplication of all cellular components before cell division. This imposes a unique biosynthetic requirement for amino acids that can be used for biomass production. Thus, the ability to sense and respond to amino acid availability is likely a major determinant for proliferation. Using a cellular and genetic approach, we demonstrate the amino acid sensor GCN2 is required to support the robust proliferative capacity of SSPC during bone homeostasis. GCN2 ablation results in decreased postnatal bone mass due primarily to reduced osteoblast numbers. Decreased osteoblast numbers is likely attributed to reduced SSPC proliferation as loss of GCN2 specifically affected proliferation in cultured bone marrow stromal cells (BMSCs) without impacting osteoblast differentiation in vitro. Mechanistically, GCN2 regulates proliferation by increasing amino acid uptake downstream of the transcriptional effector ATF4. Collectively, these data suggest amino acid sensing through the GCN2/ATF4 pathway is indispensable for robust SSPC proliferation necessary for bone homeostasis. © 2020 American Society for Bone and Mineral Research.